A concurrent working memory load does not necessarily impair spatial attention: Evidence from inhibition of return. Issue 1 (2nd January 2021) - Shen, Zhuowen; Ding, Yun; Satel, Jason; Wang, Zhiguo
ABSTRACT: Inhibition of return (IOR), an inhibitory aftereffect of attentional orienting, usually reveals itself in slower responses to targets appearing at previously attended locations in spatial cueing tasks. Many of the neural substrates underlying visual working memory are also closely linked to attention. The present study examined whether the contents held in working memory interfere with IOR by requiring participants to keep a set of spatial locations in working memory while they performed a spatial cueing task. Results revealed that the presence of a concurrent working memory load modulated IOR when the cueing task involved saccadic responses (Experiment 4), but not when more resource-demanding responses were required in the cueing task (Experiments 1–3). The present study also revealed that working memory load had little effect on the time course of IOR. We suggest that the attentional control setting (ACS) selected to accommodate the cognitive tasks at hand determines whether working memory will interfere with IOR and spatial attention in general.